Study on the Corrosive Nature of Soil Towards the Buried-Structures - Bhattarai, Jagadeesh (Scientific World, 2013)
Scientific World, Vol. 11, No. 11, July 2013, page 43-47 DOI: http://dx.doi.org/10.3126/sw.v11i11.8551